Examining The Public-Private-Partnership Tourism Toolkit as a vehicle for socioeconomic beneficiation - de Kock, Gary (Graduate School of Business (GSB), 2021)
By way of their geographic range and financial spend, South Africa's national parks have the potential for significant economic impact in the country's rural and urban areas. The research used three small-cap case studies to examine government's Public Private Partnership (PPP) Toolkit for Tourism for its ability to deliver economic benefit to communities around South African National Parks. The study identified areas of disjuncture between policy intention and policy implementation and suggests that the measures used to assess the contribution of small-cap PPPs be revised if the Toolkit is to become a meaningful instrument for small business growth and economic transformation. Findings reveal that simplifying the Toolkit bidding process is not likely to broaden entry for small businesses as the due diligence elements embedded in it are necessary to restrict corruption and abuse. Instead, it concluded that the ecosystem in which small businesses are required to operate is more important for creating economically sustainable small businesses. The most significant feature of this ecosystem would be the empowerment culture of the recipient institutions and the contractual binding of big business to enterprise development targets. The barriers to entry do not necessarily arise from the design of the Toolkit itself, but from the support institutions that have not transformed sufficiently to become the fertile grounds for the mentoring of small businesses expected of these institutions.